From classical to quantum mechanics : an introduction to the formalism, foundations, and applications - Esposito, Giampiero (Cambridge University Press, 2004)
This textbook provides a pedagogical introduction to the formalism, foundations and applications of quantum mechanics. Covering the basic material necessary to understand the transition from classical to wave mechanics, the Weyl quantisation, the postulates of quantum mechanics and many advanced topics. A textbook for beginning graduate and advanced undergraduate courses.